Kemerdekaan Berfikir dan Berteologi Kristen - Maruli Tua Tampubolon; Stefanus Dully (Syntax Corporation Indonesia, 2024)
This research discusses freedom of thought as an important element in the development of Christian theology and how the church responds to modern social challenges. Freedom of thought, although it often faces obstacles from church authority and attachment to tradition, provides opportunities for a more inclusive and progressive theological dialogue. This research uses a qualitative approach with a descriptive method, which involves in-depth interviews with church leaders and document analysis. The results show that freedom of thought contributes to enriching Christian theology and strengthens its relevance in responding to social issues, such as gender equality and social justice. This study concludes that freedom of thought plays an important role in maintaining the relevance of Christian theology in the midst of changing times without ignoring the teachings of the core faith.